Evaluation Model of Expertise Practice Programs for Early Childhood Educator Teachers - Junanto, Subar; Utami, Tri (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
This study aims to create a model for developing expertise evaluation programs at the IAIN Surakarta PIAUD Department. The research method used is development research (Research and Development). The results showed that the EPPK model produced had two-dimensional constructs, namely processes and products. The dimensions of the process of publishing in-strument planning, implementation and output. The product dimensions are complete instru-ments of dance ability, musical ability, storytelling ability and artistic ability. This EPPPK model has approved the feasibility of criteria: a. has a good format (average 79.7%), b. has approved the substance of a good evaluation model (average 79.2%), c. has a good evalua-tion procedure (average 80%). The EPPK model has a very good success rate, it is proven that expertise program lecturers can use the EPPK model easily. The results of the evaluation using the EPPK model can provide a complete and comprehensive description of the pro-gram for conducting expertise in the Surakarta IAIN PIAUD Department. Key Words: Early Childhood Education (PIAUD), Evaluation Model, Expertise Practice Programs for Early Childhood (EPPK) References Amrein-Beardsley, A., Polasky, S., & Holloway-Libell, J. (2016). Validating Bvalue added^ in the primary grades: one district’s attempts to increase fairness and inclusivity in its teacher evaluation system. Educational Assessment, Evaluation and Accountability. Educational Assessment, Evaluation and Accountability. Borg, W. R., & Gall, M. D. (1989). Educational research. New York: Longman. Briggs, D. C., & Dadey, N. (2017). Principal holistic judgments and high-stakes evaluations of teachers. Educational Assessment, Evaluation and Accountability. Cizek, B. J. (2000). Pockets of resistance ini the assessment revolution. Educational Measurement Issues and Practice Journal, 192. Elliot, R. B. (2018). Understanding Faculty Engagement in Assessment through Feedback and Dialogues: A Mixed Methods Approach. International Journal of Evaluation and Research in Education, 7(2). Eseryel, D. (2002). Approaches to evaluation of training: Theory & Practice. Educational Technology & Society, 5(2). Hallinger, P., Heck, R., & Murphy, J. (2014). Teacher evaluation and school improvement: an analysis of the evidence. Educational Assessment, Evaluation and Accountability. Hasan, H. (2009). Evaluasi Kurikulum (II). Bandung: PT Remaja Rosdakarya. Herpich, S., & Pratoreus, K. A. (2018). Teachers’ assessment competence: Integrating knowledge-, process-, and product-oriented approaches into a competence-oriented conceptual model. Teaching and Teacher Education. Meng, L., & Muñoz, M. (2016). Teachers’ perceptions of effective teaching: a comparative study of elementary school teachers from China and the USA. Educational Assessment, Evaluation and Accountability.Ovretveit, J. (2002). Evaluation of quality improvement programmes. Quality and Safety in Health Care, 11(3), 270–275. https://doi.org/10.1136/qhc.11.3.270 Podsakoff, P. M., MacKenzie, S. B., Moorman, R. H., & Fetter, R. (2015). Transformational Leader Behaviors and Their Effects on Trust , Satisfaction , and Organizational Citizenship Behaviors. JAI Press Inc., (August), 107–142. https://doi.org/10.1016/1048-9843(90)90009-7 Roegman, R., Goodwin, A. L., & Reed, R. (2016). Unpacking the data: an analysis of the use of Danielson’s (2007) Framework for Professional Practice in a teaching residency program. Educational Assessment, Evaluation and Accountability. Seng, K.-H., Diez, C. R., Lou, S.-J., Tsai, H.-L., & Tsai, T.-S. (2010). Using the Context, Input, Process and Product model to assess an engineering curriculum. World Transactions on Engineering and Technology Education, 8(3). Skedsmo, G., & Huber, S. G. (2016). Teacher evaluation—accountability and improving teaching practices. Teacher Evaluation—Accountability and Improving Teaching Practices. Skedsmo, Guri, & Huber, S. G. (2018). Teacher evaluation: the need for valid measures and increased teacher involvement. Educational Assessment, Evaluation and Accountability, 30(1), 1–5. https://doi.org/10.1007/s11092-018-9273-9 Steinert, Y., Cruess, S., Cruess, R., & Snell, L. (2005). Faculty development for teaching and evaluating professionalism: From Programme Design To Curriculum Change. Medical Education. Stufflebeam, D. L. (2003). The CIPP model for evaluation. Oregon Program Evaluators Network. Uerz, D., Vorman, M., & Kral, M. (2018). Teacher educators’ competences in fostering student teachers’ proficiency in teaching and learning with technology: An overview of relevant research literature. Teaching and Teacher Education. Vrasidas, C. (2000). Constructivism Versus Objectivism: Implications for interaction, Course Design, And Evaluation In Distance Educatio. International Journal of Educational Telecommunications, 6(4). Wahyuni, A., & Kartawagirun, B. (2018). Developing Assessment Instrument Of Qirāatul Kutub At Islamic Boarding School. Jurnal Penelitian Dan Evaluasi Pendidikan, 22(2).